Analisis Elemen Dukungan Orang Tua terhadap Anak SD Kelas 1-2 dalam Tingkat Kefokusan Menerima Pembelajaran Daring di SDN Pasiraman 03 Kabupaten Blitar - Dily Ekasari; Astri Yunita; Khetrina Anisa Putri (Indonesian Journal on Medical Science, 2022)
Parental support in child focus is any form of parental assistance or support in the form of emotional, instrumental, informational and assessment or reward. The purpose of this study is to find out the relationship of parental support elements to elementary children in grades 1-2 in the focus level of receiving online learning during the COVID-19 pandemic. The research method used quantitative method with a cross sectional approach. The sample was taken with purposive sampling techniques as many as 30 respondents. The data was collected using questionnaires and analyzed with the Pearson Product Moment test. The results showed that parental support was emotional support with values p =0.013 and r (0.446), instrumental support with values p =(0.013) and r (0.448), informational support with values p =0.031 and r (0.394), and assessment or reward support with values p =(0.012) and r (0.453) for elementary children grades 1-2 most of the respondents had good parental support. The study's conclusion suggest there is a link between parental support for a child's level of  focus during online learning. Parental support in the era of the COVID-19 pandemic is very important to be able to increase the level of focus of children in receiving online learning.